2003
DOI: 10.1177/016264340301800302
|View full text |Cite
|
Sign up to set email alerts
|

Assistive Technology Integration in Special Education Teacher Preparation: Program Coordinators' Perceptions of Current Attainment and Importance

Abstract: This article reports findings from a national survey of special education teacher preparation programs regarding the integration of assistive technology (AT) into curriculum and instruction. Two questions framed this research. The first focused on how AT knowledge, skills, and dispositions are currently integrated (the Current Attainment Level), and the second focused on how AT should ideally be integrated (the Importance). All paired t tests between Current Attainment Level and Importance were statistically s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
0
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 14 publications
3
36
0
4
Order By: Relevance
“…The infusion of AT content into existing courses in the special education teacher program has been advocated but in reality is difficult to achieve (Bausch & Hasselbring, 2004;Lahm & Nickels, 1999). If programs choose to infuse AT into the curriculum, it is usually either through providing students with a basic overview of AT in the introductory courses or it is up to each professor to integrate AT into their courses (Michaels & McDermott, 2003). To properly infuse AT into special education teacher training programs may require a complete overhaul of courses so that all content is more integrated and aligned with AT standards.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The infusion of AT content into existing courses in the special education teacher program has been advocated but in reality is difficult to achieve (Bausch & Hasselbring, 2004;Lahm & Nickels, 1999). If programs choose to infuse AT into the curriculum, it is usually either through providing students with a basic overview of AT in the introductory courses or it is up to each professor to integrate AT into their courses (Michaels & McDermott, 2003). To properly infuse AT into special education teacher training programs may require a complete overhaul of courses so that all content is more integrated and aligned with AT standards.…”
Section: Discussionmentioning
confidence: 99%
“…The success of students with disabilities using AT is related directly to the AT knowledge and skills of special education teachers. In a recent national survey of AT integration in graduate special education teacher preparations programs, results indicated that many graduates are leaving special education teacher preparation programs without the critical knowledge, skills, and dispositions necessary to address the AT needs of their students (Michaels & McDermott, 2003). They found a significant difference between what current special education teacher preparation programs provide in training teachers to use and integrate AT into the classroom and what the coordinators of these university programs believe is necessary for successful AT integration.…”
mentioning
confidence: 99%
“…Additionally, early intervention providers and Part C coordinators are more likely to describe assistive technology as those devices that are considered high-tech and not readily available and that more often fit the definition of durable medical equipment . A growing body of literature indicates that the successful use of assistive technology by children is related to the experience, expertise, and attitudes regarding assistive technology and assistive technology services of the service providers (Michaels & McDermott, 2003).…”
mentioning
confidence: 99%
“…For example, students may use word processors to accomplish their assignments and manage linguistic errors (Montgomery and Marks, 2006). Using technology with students with disabilities is advantageous in their educational outcomes (Michaels and McDermott, 2003;Schlosser and Wendt, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…There is a need to understand the barriers to technology faced by teachers as this might be helpful in technology integration (Schoepp, 2005). Among these barriers are access issues, professional experience and family involvement (Dissinger, 2003;Michaels and McDermott, 2003;Smith and Allsopp, 2005). Financial restraints such as purchase, maintenance and replacement of equipment on both families and schools may hinder technological interventions (Edyburn, 2006).…”
Section: Introductionmentioning
confidence: 99%